Diagenetic evolution of clay minerals and impacts on reservoir quality of the Wufeng and Longmaxi Shale in Sichuan Basin of China - Yang Chen; Jianhua Zhao; Qinhong Hu; Keyu Liu; Mengxiang Yu; Wei Wu; Chao Luo (Applied Clay Science, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Developmental stage-specific disruption of iron allocation by a ZmYSL2 mutation in maize - Yikai Wang; Kunfeng Zhang; Chuang An; Jiayi Liu; Hongmei Hu; Duo Shi; Jiaxin Shi; Keyu Zhao; Dan Liu; Ling Wu; Xiao Zhang; Bowen Luo; et al. (Planta, 2026)

Grazing-induced enhancement of rhizosphere effect on soil multifunctionality is linked to altered microbial life-history strategies in semiarid grasslands - Nuo Xu; Le Li; Yuhong Luo; Yunxiang Jin; Keyu Bai; Qiuli Bao; Jiahui Liu; Yufan Bao; Yuchun Yan (Agriculture, Ecosystems & Environment, 2026)

First Case of Nocardia seriolae Infection in China Cultured Channel Catfish ( Ictalurus punctatus ) - Mingqi Ai; Keyu Zhou; Qibin Jiang; Kun Peng; Yilin Wang; Yiteng Luo; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Journal of Fish Diseases, 2026)
Nocardia seriolae is a causative agent for fish skin ulcers and sarcoidosis, resulting in significant losses in both brackish and freshwater fish farming industries. From October to November 2023, channel catfishes ( Ictalurus punctatus ) cultured in Xiaowan reservoir at Dali city, Yunnan province in China, showed gross pathological changes with skin ulcers, white nodules in the liver and heart, histopathological tests revealed the typical granulomas and chronic hepatitis changes in the liver, and the clumps of filamentous bacteria in the heart and spleen. A Gram‐positive acid‐fast bacterium (CCF_NS01) was isolated from viscera (liver, spleen and kidney); biochemical tests and 16sRNA‐GyrB gene concatenated sequences analysis of this isolated microorganism identified it as N. seriolae . Drug sensitivity testing indicated susceptibility to commonly used antibiotics such as co‐trimoxazole, doxycycline, enrofloxacin, florfenicol, amikacin and rifampicin. In isolated CCF_NS01, multiple pathogenic factors corresponding to encoding genes were detected, including espG , mftF , pcaA , fadD32 , pks13 , narJ , feoB , sodA , katG and mceF . 100% mortality with 1 × 10 8 , 1 × 10 7 and 1 × 10 6 cfu/mL in a 35‐d challenge test period was observed, and the intraperitoneal injection median lethal dose (LD 50 ) was 1.89 × 10 4 cfu/mL. This is the first isolation report of N. seriolae infection from cultured channel catfish, aiming to warn against the continuous host‐range expansion of this pathogen, which is threatening the inland aquaculture industry.

Modelling the socio-ecological security pattern for large freshwater lake regions: supply-demand mismatch in the Dongting lake area - Zhenyu Wang; Yuhao Gong; Le Xia; Keyu Luo; Tao Jiang; Yi Ying; Miaomiao Xie (Environment, Development and Sustainability, 2026)

Modelling green space accessibility and equity in mountainous cities: a case study of Chongqing - Yuhan Wang; Keyu Luo; Zhenyu Wang; Meichen Fu (Environment, Development and Sustainability, 2025)

Pyrite-based reconstruction of seawater trace metal concentration in Earth history: Insights from abiotic synthesis experiments - Keyu Zhu; Zhaoyi Dai; Deng Liu; Genming Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

Regulation of astaxanthin accumulation in Phaffia rhodozyma under titanium dioxide and rapeseed oil stress by amino acid metabolism - Meizhen Liu; Tiantian Han; Lu Luo; Ying Zhang; Gaofeng Yuan; Xubo Fang; Keyu Dong; Jing Zhang; Xiaoe Chen (Food Chemistry, 2025)

How does greenness contribute to reducing lung cancer risks associated with particulate matter exposure? - Keyu Luo; Huagui Guo; Weifeng Li; Jiansheng Wu (Atmospheric Pollution Research, 2025)

Unleashing hidden carbon sequestration potential: A case study of the Greater Bay Area, China - Keyu Luo; Zhenyu Wang; Weifeng Li; Jiansheng Wu (Urban Climate, 2024)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Impact of chlorites on the wettability of tight oil sandstone reservoirs in the Upper Triassic Yanchang Formation, Ordos Basin, China - Zhongnan Wang; Xiaorong Luo; Keyu Liu; Yuchen Fan; Xiangzeng Wang (Science China Earth Sciences, 2021)

Towards Realizing Intelligent Coordinated Controllers for Multi-USV Systems Using Abstract Training Environments - Sulemana Nantogma; Keyu Pan; Weilong Song; Renwei Luo; Yang Xu (Journal of Marine Science and Engineering, 2021)
Unmanned autonomous vehicles for various civilian and military applications have become a particularly interesting research area. Despite their many potential applications, a related technological challenge is realizing realistic coordinated autonomous control and decision making in complex and multi-agent environments. Machine learning approaches have been largely employed in simplified simulations to acquire intelligent control systems in multi-agent settings. However, the complexity of the physical environment, unrealistic assumptions, and lack of abstract physical environments derail the process of transition from simulation to real systems. This work presents a modular framework for automated data acquisition, training, and the evaluation of multiple unmanned surface vehicles controllers that facilitate prior knowledge integration and human-guided learning in a closed-loop. To realize this, we first present a digital maritime environment of multiple unmanned surface vehicles that abstracts the real-world dynamics in our application domain. Then, a behavior-driven artificial immune-inspired fuzzy classifier systems approach that is capable of optimizing agents’ behaviors and action selection in a multi-agent environment is presented. Evaluation scenarios of different combat missions are presented to demonstrate the performance of the system. Simulation results show that the resulting controllers can achieved an average wining rate between 52% and 98% in all test cases, indicating the effectiveness of the proposed approach and its feasibility in realizing adaptive controllers for efficient multiple unmanned systems’ cooperative decision making. We believe that this system can facilitate the simulation, data acquisition, training, and evaluation of practical cooperative unmanned vehicles’ controllers in a closed-loop.